Detection and quantification of natural Wolbachia in Aedes aegypti in Metropolitan Manila, Philippines using locally designed primers - Reyes, Jerica Isabel L.; Suzuki, Takahiro; Suzuki, Yasutsugu; Watanabe, Kozo (Frontiers in Cellular and Infection Microbiology, 2024)
Background The Philippines bears health and economic burden caused by high dengue cases annually. Presently, the Philippines still lack an effective and sustainable vector management. The use of Wolbachia, a maternally transmitted bacterium, that mitigate arbovirus transmission has been recommended. Cytoplasmic incompatibility and viral blocking, two characteristics that make Wolbachia suitable for vector control, depend on infection prevalence and density. There are no current Wolbachia release programs in the Philippines, and studies regarding the safety of this intervention. Here, we screened for Wolbachia in Aedes aegypti collected from Metropolitan Manila, Philippines. We designed location-specific primers for qPCR to test whether this improved Wolbachia detection in Ae. aegypti. We explored if host sex and Wolbachia strain could be potential factors affecting Wolbachia density. Methods Ae. aegypti mosquitoes (n=429) were screened for natural Wolbachia by taqman qPCR using location-specific Wolbachia surface protein primers (wspAAML) and known 16S rRNA primers. Samples positive for wspAAML (n=267) were processed for Sanger sequencing. We constructed a phylogenetic tree using IQ-TREE 2 to further characterize Wolbachia present in the Philippine Ae. aegypti. We then compared Wolbachia densities between Wolbachia groups and host sex. Statistical analyses were done using GraphPad Prism 9.0. Results Wolbachia prevalence for 16S rRNA (40%) and wspAAML (62%) markers were high. Wolbachia relative densities for 16S rRNA ranged from −3.84 to 2.71 and wspAAML from −4.02 to 1.81. Densities were higher in male than female mosquitoes. Wolbachia strains detected in Ae. aegypti clustered into supergroup B. Some 54% (123/226) of these sequences clustered under a group referred to here as “wAegML,” that belongs to the supergroup B, which had a significantly lower density than wAegB/wAlbB, and wAlbA strains. Conclusion Location-specific primers improved detection of natural Wolbachia in Ae. aegypti and allowed for relative quantification. Wolbachia density is relatively low, and differed between host sexes and Wolbachia strains. An economical way of confirming sporadic or transient Wolbachia in Ae. aegypti is necessary while considering host sex and bacterial strain.